EVALUATION OF THE TREATMENT EFFICACY OF TIGECYCLINE AND REISHI SHIITAKE MAITAKE MUSHROOM EXTRACT IN MICE WITH THE VISCERAL LEISHMANIASIS MODEL - Özden Büyükbaba Boral; Deniz Gözde Çelik Payçu; Halim İşsever (İstanbul Tıp Fakültesi Dergisi)
Objective: Visceral leishmaniasis (VL) is an infection that can be fatal if left untreated. Treatment of VL is becoming increasingly difficult due to the development of resistance to some drugs used. We aimed to investigate the efficacy of tigecycline (Tig) and Reishi-Shiitake-Maitake (RSM) mushroom extract alone and in combination in BALB/c mice infected with the Leishmania donovani strain (ATCC 30030). Materials and Methods: To compare the treatment efficacy, the mice that were treated with amphotericin B (AMB) were used as the control group. BALB/c mice (n=40) were intravenously inoculated in the lateral vein of the tail with 107 stationary-phase L. donovani promastigotes in 100 µL of PBS. BALB/c mice were divided into 5 groups of 8. Tig group received 3.7 mg/kg tigecycline intraperitoneally for 5 days, RSM group received 10 mg/ kg RSM extract by oral gavage for 5 days while Tig+RSM group received the same doses of both drugs via the same routes. Also, the AMB group received 15mg/kg amphotericin B by oral gavage for 5 days. The spleen and liver of all mice that were sedated with ketamine were collected on the 12th day. Parasite load was determined by Leishman Donovan Unit (LDU) and quantitative RT-PCR. Results: When all groups were statistically evaluated according to LDU and RT-PCR findings, the lowest value was obtained in the AMB group compared to the value in the control group, while the second lowest value was obtained in the Tig+RSM group. Thedata obtained in the Tig+ RSM group were significantly lower than the data in other groups, except for the AMB group. Conclusion: Our study suggested that the use of RSM extract together with tigecycline may be an alternative in the treatment of VL. Further studies using different doses and routes of administration are needed to evaluate the efficacy of this combination.